Meningkatkan Keaktifan Belajar pada Pelajaran Biologi Menggunakan Model Problem Based Learning disertai Media Video - Patmawati Patmawati; Meilinda Meilinda (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
This research was conducted because of the problem of low learning activeness in students. This research is focused on making students in class XI MIA 5 at SMAN 10 Palembang become more active in the learning process. In an effort to carry out this research, the Classroom Action Research (CAR) approach was used and the application of the Problem Based Learning (PBL) model. This study involved 2 cycles, with each cycle consisting of 2 meetings involving 30 research subjects. Data collection in this study was an observation sheet of students' active learning which was validated using CVI. In the results obtained, it is known that there is an increase in student activity on an ongoing basis in each cycle which in cycle 1 meeting 1 was 58% to 66% at meeting 2, then in the second stage of the cycle, there was an increase from 70% to 80% at the second meeting. Based on these data it can be seen that in cycle II, the research was said to be successful by obtaining very good information. From the results of the research, it is said that applying the PBL model accompanied by video media is able to increase the activity of students in class.